132 Targeted Resuscitation Using Echocardiography in a Military Ebola Virus Disease Treatment Unit. (6th June 2015) - Rees, Paul; Ardley, Christian; Lamb, Lucy; Fletcher, Thomas; Bailey, Mark; Dickson, Stuart; Nicholson-Roberts, Timothy; Hinsley, David; Sam, Hutchings
Abstract : Introduction: Patients with Ebola virus disease (EVD) frequently suffer from haemodynamic instability and shock, leading to multiple organ failure and death. Clinical assessment of circulatory status is extremely challenging in these patients, hampered by the need for physicians to wear restrictive personal protective equipment, and adverse environmental factors within the EVD treatment unit (EVDTU). No EVDTUs currently use invasive cardiac output monitoring. Transthoracic echocardiography (TTE) can be used to assess haemodynamic status in critical care resuscitation. Additionally, the incidence of pericardial effusion in Ebola virus disease (EVD) is unknown. We describe the use of focused TTE (fTTE) in a military EVDTU in Sierra Leone. Methods: Baseline fTTE was performed early during the admission of all patients presenting with confirmed EVD and haemodynamic instability. Studies were performed by either a consultant cardiologist or intensivist. The median duration of EVD was 6 days prior to initial fTTE (range 3–7). In some cases, serial studies were performed during admission. Data were collected on haemodynamics, TTE view availability, LV function, presence of pericardial effusion, IVC dimensions and variability with respiration. Where central venous catheter (CVC) insertion was performed, fTTE was used to check placement by visualisation of the CVC tip, and modified views were used to exclude pneuomothorax, as no radiology facility exists within the EVDTU. Results: During the first 4 weeks of operation, 8 patients with Ebola virus disease and haemodynamic instability underwent fTTE examination. TTE windows available were as follows: parasternal long axis 60%, parasternal short axis 60%, apical 4 chamber 90%, subcostal 100%. IVC imaging was possible in 80% of cases. All hearts examined were structurally normal. LV function was normal in all cases (EF >55%). Small pericardial effusions (mean 0.58 cm, ) were found in 3 cases (37.5%). In 3 cases, hypovolaemia was so profound that LV systolic cavity obliteration was noted. The mean maximal IVC diameter in studies performed during inital resuscitation was 1.73 (±0.05) cm, compared with 2.10 (±0.18) in a partially resuscitated cohort. In 90% of studies, fTTE findings supported continued intravascular volume expansion. In one case, fTTE values suggested that further filing was not required, resulting in a change in management strategy. In studies following CVC placement (n = 9) the tip of the device was visualised in all cases, and lung imaging confirmed no cases of pneumothorax. Conclusions: This study demonstrates, for the first time in a deployed military Ebola virus disease treatment unit, that fTTE can assist with assessment of volume status during the resuscitation phase. In addition, the incidence of pericardial effusion appears to be low.